Total Brain Workout Vol II : To Sharpen Your Mind Improve Your Memory & Keep Your Brain Fit - Marcel Danesi (Harlequin India Pvt. Ltd, 2009)
Did you know that different parts of your brain control different functions and that with exercise, you can make each part of your brain stronger? In The Total Brain Workout youll find fun, challenging and absorbing puzzles designed to specifically target the core parts of your brain that control language, logic, memory, reasoning and visual perception. Each set of puzzles range from easy to challenging and is presented with information on the area of your brain being targeted and the functions it controls, so you can customize your own workout to the specific areas you want to improve.